PERIODS OF WEED INTERFERENCE ON TRANSGENIC COTTON ‘IMACD 6001LL’ - Silva, Marcos Paulo da (2016)
The objective of this study was to determine the periods of weed interference and its impact on productivity of cotton 'IMACD 6001LL'. The experiment was conducted in Jaboticabal, São Paulo, the second crop in 2011 and consisted of two treatment groups: the first culture remained free of competing weeds since of emergence up different periods of its development: (0-15 , 0-25, 0-35, 0-45, 0-55, 0-65, 0-75 and 0-183 days - harvest). In the second treatment group was held to the contrary: the crop was in harmony with the weeds since of emergence up to the same stages of development described above. The treatments were arranged in a randomized block design in four replications. During these periods was evaluated dry matter accumulation by weeds. The cotton yield data were subjected to regression analysis and resulting in a CPWC of 35 DAE, the CPWR was 133 DAE and .The weed community was composed mainly of Raphanus raphanistrum, Amaranthus spp., Cyperus rotundus, Alternanthera tenella and Eleusine indica. Living with this community throughout the cycle resulted in reduction almost 85% in cotton yield.